Identification of Potential Silvo-Ecotourism Objects In The Mangsang Forest Area, Sei Beduk District, Batam Island - febrianti Lestari; diana azizah; Rezal Hadi Basalamah (Jurnal Penelitian Kehutanan BONITA, 2024)
The potential for ecotourism in the Riau Islands has increased after the Covid 19 pandemic passed, with the largest number of foreign tourist destinations on Batam Island. One of the ecotourism potentials that can be developed is land forest management as part of the forest and land rehabilitation program by BPDASHL Sei Jang Duriangkang Riau Islands in Mangsang Village, Sei Beduk District. Several ecotourism activities have been developed but have not been managed well. One of the efforts to manage sylvo-ecotourism in Mangsang can be done by identifying sylvo-ecotourism potential. Identification was carried out by surveying and exploring the forest area around Mangsang Hill, Sei Beduk District. The data collected includes the type and condition of land forests, unique, interesting and rare types of fauna as well as potential tourism activities that can be developed. Based on the results, it was found that there is sylvo-ecotourism potential for sports spots such as downhill, tracking; natural spots such as the Mangsang waterfall and views of sunset, sunrise and views of the coast and islands around Batam City; as well as agricultural fruit harvest spots. It is feared that land clearing activities around the Predatory Hill area for settlement will cause sedimentation due to erosion around the Tembesi Reservoir.